1989
DOI: 10.1021/j100343a068
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state NMR study using trimethylphosphine as a probe of acid sites in normal and dealuminated zeolite Y

Abstract: spectra of adsorbed CO may be assessed. Magic-angle spinning yields precise isotropic shifts and thus could detect subtle changes in the properties of the adsorption site caused by, for example, promoters or coadsorbates. However, magic-angle spinning spectra of adsorbed CO should not be used to exclude the existence of some species. As noted above, the bridge-bonded species do not appear and could be overlooked if the lack of agreement between the center of mass of the broad-line and high-resolution spectra w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
2

Year Published

1999
1999
2008
2008

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 0 publications
4
53
0
2
Order By: Relevance
“…As a consequence, the number of acid sites in zeolites is underestimated. This is in agreement with the quantitative TMP adsorption study carried out by Lunsford et al [28] Discussion When a basic ligand, L (including water), is adsorbed on the zeolite surface, it reacts with both the Br˘nsted, to form SiÀOHLÀAl, and Lewis acid sites. A comparison between the 27 Al MAS and CP/MAS NMR spectra of hydrated and ammonia-adsorbed zeolite samples (Figures 1 and 5) reveals that: 1) Al is invisible to 27 Al MAS NMR in the case of strictly dehydrated zeolite samples and 2) once the adsorbent is loaded, the electric-field gradient at Al is sufficiently reduced to render Al to be detectable by NMR spectroscopy.…”
Section: Resultssupporting
confidence: 90%
“…As a consequence, the number of acid sites in zeolites is underestimated. This is in agreement with the quantitative TMP adsorption study carried out by Lunsford et al [28] Discussion When a basic ligand, L (including water), is adsorbed on the zeolite surface, it reacts with both the Br˘nsted, to form SiÀOHLÀAl, and Lewis acid sites. A comparison between the 27 Al MAS and CP/MAS NMR spectra of hydrated and ammonia-adsorbed zeolite samples (Figures 1 and 5) reveals that: 1) Al is invisible to 27 Al MAS NMR in the case of strictly dehydrated zeolite samples and 2) once the adsorbent is loaded, the electric-field gradient at Al is sufficiently reduced to render Al to be detectable by NMR spectroscopy.…”
Section: Resultssupporting
confidence: 90%
“…The chemical exchange of pyridine molecules at different adsorption sites with different cross-polarization efficiencies renders a quantitative evaluation difficult [210]. In a number of studies on zeolite acidity, the strong base trimethylphosphine (TMP) was used as a probe molecule [420][421][422]. Since the isotope 31p occurs in a natural abundance of 100 %, this method does not necessarily require the application of the CP technique.…”
Section: Investigations Of Brnsted and Lewis Acid Sites By Probe Molmentioning
confidence: 99%
“…These investigations have shown that TMP is a sensitive NMR probe molecule for acidity measurements. However, TMP is a rather large molecule and the determination of acid sites in zeolites is therefore restricted by the maximum adsorption capacity of the pore system as well as steric hindrances [421]. In another approach, Biaglow et al [423] [425], and Brunner et al [323,426].…”
Section: Investigations Of Brnsted and Lewis Acid Sites By Probe Molmentioning
confidence: 99%
“…Therefore, many compounds containing 31 P have been used as probe molecules to determine the zeolite acidity. Especially, trimethylphosphine, with a pK b of 5.35, has been widely used for the characterization of acidity in zeolites such as H-Y and USY [20,21]. In this work, the acidity of TS-1 was studied using trimethylphosphine as the probe molecule.…”
Section: Acidity In Ts-1 Zeolitesmentioning
confidence: 99%